The Arabidopsis NRT1.1 transceptor coordinately controls auxin biosynthesis and transport to regulate root branching in response to nitrate. (19th May 2020) - Maghiaoui, Amel; Bouguyon, Eléonore; Cuesta, Candela; Perrine-Walker, Francine; Alcon, Carine; Krouk, Gabriel; Benková, Eva; Nacry, Philippe; Gojon, Alain; Bach, Liên
Abstract : The NRT1.1 transceptor controls upstream auxin biosynthesis for emergence of lateral root primordia and downstream action of auxin for lowering mechanical resistance of primary root tissues, allowing outgrowth of lateral root primordia. Abstract: In agricultural systems, nitrate is the main source of nitrogen available for plants. Besides its role as a nutrient, nitrate has been shown to act as a signal molecule in plant growth, development, and stress responses. In Arabidopsis, the NRT1.1 nitrate transceptor represses lateral root (LR) development at low nitrate availability by promoting auxin basipetal transport out of the LR primordia (LRPs). Here we show that NRT1.1 acts as a negative regulator of the TAR2 auxin biosynthetic gene in the root stele. This is expected to repress local auxin biosynthesis and thus to reduce acropetal auxin supply to the LRPs. Moreover, NRT1.1 also negatively affects expression of the LAX3 auxin influx carrier, thus preventing the cell wall remodeling required for overlying tissue separation during LRP emergence. NRT1.1-mediated repression of both TAR2 and LAX3 is suppressed at high nitrate availability, resulting in nitrate induction of the TAR2 and LAX3 expression that is required for optimal stimulation of LR development by nitrate. Altogether, our results indicate that the NRT1.1 transceptor coordinately controls several crucial auxin-associated processes required for LRP development, and as a consequence that NRT1.1 plays a much more integrated role than previously expected in regulating the nitrate response of root system architecture.